Social Representation of Family-School Relationship from Initial Teacher Training - Héctor Cárcamo Vásquez; Jordi Garreta Bochaca (Universidad Autónoma de Baja California, 2020)
The paper presents the representations that future elementary school teachers have in a University of Ñuble region for the family and parental roles assigned to them in education. In line with the objective, a comprehensive interpretive study using qualitative methodology is developed. Among the most important findings we found that roles that subjects assign families are located in two clearly defined dimensions; on one hand, support on the educational field through the completion school duties and, secondly, the inculcation of habits that facilitate the establishment of a classroom climate in favor of learning.